2009
DOI: 10.1016/j.jasms.2008.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser photoionization time-of-flight mass spectrometry of nitro-aromatic explosives and explosives related compounds

Abstract: The ultrafast laser-induced photoionization and photodissociation processes of the nitroaromatic containing explosive and explosive related compounds (ERCs) nitrobenzene (NB), 1,3-dinitrobenzene (DNB), m-nitrotoluene (MNT), 2,4-dinitrotoluene (DNT), and 2,4,6-trinitrotoluene (TNT) have been investigated at three laser wavelengths and power densities using a time-of-flight mass spectrometer. Examination of the mass spectra of these compounds reveals the enhanced formation of the molecular ion [M ϩ ] when ultrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
36
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 52 publications
4
36
1
Order By: Relevance
“…On increasing the energy to 0.40 mJ/pulse (0.65 J/cm 2 ), a well‐resolved mass spectrum is observable with information in the high‐mass range. As in related work, our spectra did not show signals associated to 46 NO 2 . This is because the short lifetime of the intermediate states involved in the generation of NO 2 + (a few hundred femtoseconds) leads to rapid dissociation to generate the most stable NO + ion …”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…On increasing the energy to 0.40 mJ/pulse (0.65 J/cm 2 ), a well‐resolved mass spectrum is observable with information in the high‐mass range. As in related work, our spectra did not show signals associated to 46 NO 2 . This is because the short lifetime of the intermediate states involved in the generation of NO 2 + (a few hundred femtoseconds) leads to rapid dissociation to generate the most stable NO + ion …”
Section: Resultssupporting
confidence: 83%
“…Thermal decomposition chemistry is fundamentally important in the explosives field, and the determination of the kinetics and mechanisms of the thermal decomposition remains a fundamental aspect of their characterization. Laser‐based mass spectrometry has proved to be a useful method for the characterization of these families of compounds . Moreover, the use of mass spectrometry in studies of the products of decomposition and detonation of explosives has been important as it helped to determine the chemical fragmentation pathways which lead to the dissociation of the parent molecules .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that ultraviolet and visible wavelengths are better at generating the molecular ion than 795 nm irradiation. In addition, the effect of Coulomb explosion in the photoionization of nitroaromatic compounds has been revealed (Mullen, Coggiola, & Oser, 2009). In study of TATP, femtosecond laser was utilized for both detection of the molecular ion and enhancement of sensitivity leading to detection limit of 670 pg to the molecular ion.…”
Section: Other Ionization Techniquesmentioning
confidence: 99%
“…Finally, selectivity of ionization can be achieved by choosing the appropriate reagent ions through which chemical ionization occurs, although oxygen is an excellent reagent gas itself.One successful group of ion sources for API is that of the light-based sources. Photoionization is one such technique that utilizes either very high photon energies from vacuum UV lamps [2,3] or lasers [4] to result in Single Photon Ionization (SPI) or, when a laser is focused to give high photon flux, resulting in Multi-Photon Ionization (MPI) [5,6] or Resonant Enhanced Multi-Photon Ionization (REMPI). [7][8][9] Higher photon fluxes with laser sources permit the use of lower per-photon energies, such as with MPI or REMPI, but this process becomes less efficient at atmospheric pressure due to collisional quenching.…”
mentioning
confidence: 99%